Molecular epidemiology and environmental contamination during an outbreak of parainfluenza virus 3 in a haematology ward. Issue 4 (December 2017) - Kim, T.; Jin, C.E.; Sung, H.; Koo, B.; Park, J.; Kim, S.-M.; Kim, J.Y.; Chong, Y.P.; Lee, S.-O.; Choi, S.-H.; Kim, Y.S.; Woo, J.H.; et al.
Summary: Background: Although fomites or contaminated surfaces have been considered as transmission routes, the role of environmental contamination by human parainfluenza virus type 3 (hPIV-3) in healthcare settings is not established. Aim: To describe an hPIV-3 nosocomial outbreak and the results of environmental sampling to elucidate the source of nosocomial transmission and the role of environmental contamination. Methods: During an hPIV-3 outbreak between May and June 2016, environmental surfaces in contact with clustered patients were swabbed and respiratory specimens used from infected patients and epidemiologically unlinked controls. The epidemiologic relatedness of hPIV-3 strains was investigated by sequencing of the haemagglutinin–neuraminidase and fusion protein genes. Findings: Of 19 hPIV-3-infected patients, eight were haematopoietic stem cell recipients and one was a healthcare worker. In addition, four had upper and 12 had lower respiratory tract infections. Of the 19 patients, six (32%) were community-onset infections (symptom onset within <7 days of hospitalization) and 13 (68%) were hospital-onset infections (≥7 days of hospitalization). Phylogenetic analysis identified two major clusters: five patients, and three patients plus one healthcare worker. Therefore, seven (37%) were classified as nosocomial transmissions. hPIV-3 was detected in 21 (43%) of 49 environmental swabs up to 12 days after negative respiratory polymerase chain reaction conversion. Conclusion: At least one-third of a peak season nosocomial hPIV-3 outbreak originated from nosocomial transmission, with multiple importations of hPIV-3 from the community, providing experimental evidence for extensive environmental hPIV-3 contamination. Direct contact with the contaminated surfaces and fomites or indirect transmission from infected healthcare workers could be responsible for nosocomial transmission.